Application of Linear Algebra in Enhancing Artificial Intelligence Techniques (Comprehensive Journal of Science, 2025)
his paper examines the fundamental relationship between linear algebra and artificialintelligence techniques, as linear algebra represents the fundamental framework upon which manymachine learning algorithms are based.By analyzing mathematical concepts such as matrices, vectors, eigenvalues, and singular valuedecomposition (SVD), we highlight how these concepts can be harnessed to improve theperformance of intelligent models and develop effective techniques for data analysis, classification,and prediction. We also present applied experiments that demonstrate the practical use of linearalgebra in modern artificial intelligence models